Inhibitory Effect of Spices on Beta Lactamase Enzyme of Resistant Bacteria isolated from Milk of Healthy Cattle. - Shrivastav, Arpita; Poojitha, Dr. Ravipati; Shrivastava, Dr Neeraj; Kumar, Nitesh; Singh, Swatantra; Ranjan, Rajeev; Jha, Dr Amit Kumar (Indian Journal of Dairy Science, 2023)
Present study was undertaken to observe the effect of spices on the extended Spectrum beta lactamase enzyme of ESBL Producing Enterobacteriaceae Group of Bacteria isolated from healthy cattle milk. Out of 100 samples collected randomly from various dairy farms located at the different areas of Rewa 14 samples characterized by the phenotypic standard methods were found to be ESBL positive giving a prevalence rate of 14%. Inhibitory potential and per cent inhibition of beta lactamase enzyme were observed against dry powder of Methi seeds (Trigonella foenum-graecum), dry zinger, (Zingiberofficinale), Ajwain seeds (Trachyspermum ammi) Kalonji seeds (Nigella sativa), Black pepper (Piper nigrum), Clove bud (Syzigium aromaticum) (10mg/ml) and one test drug Tazobactum by colorimetric assay method performed on the individual spices and in their different combinations on the basis of absorbent value. The absorbance level of each spice was observed using NITROCEFIN as a chromogenic substrate at 405nm wavelength. Minimum absorbance value was observed by Zingiber officinale (0.48 ± 0.009) and the maximum absorbance value of Syzgium aromaticum (1.698 ± 0.069). The inhibitory effect of combination of the spices showed maximum absorbance value (0.46 ± 0.06) by Piper nigrum and Zingiber officinale No significant difference was seen between the absorbance value of Z.officinalis, N.sativa (0.61± 0.05) and P.nigrum T.faenum graecum (0.62±0.03). Study observed the in vitro inhibitory potential present in the spices and could be used in near future to combat antimicrobial resistance to some extent.